Biliary complications after liver transplantation; recent developments in etiology, diagnosis and endoscopic treatment. Issue 2 (April 2017) - Roos, Floris J.M.; Poley, Jan-Werner; Polak, Wojciech G.; Metselaar, Herold J.
Abstract: Biliary complications are considered to be the Achilles' heel of liver transplantation. The most common complications are leaks and bile duct strictures. Strictures can arise at the level of the anastomosis (anastomotic strictures; AS) or at other locations in the biliary tree (non-anastomotic strictures; NAS). Endoscopic treatment via endoscopic retrograde cholangiopancreatography (ERCP) is considered to be the preferred therapy for these complications. This review will focus on the diagnostic modalities, new insights in etiology of biliary complications and outcomes after different endoscopic therapies, in both deceased donor transplantation and living-donor liver transplantations. Advances in recent therapies, such as the use of self-expendable metal stents (SEMS) and endoscopic therapy for patients with a bilio-digestive anastomosis will be discussed.